Population decline of northern dusky salamanders at Acadia National Park, Maine, USA - Bank, Michael S.; Crocker, Jeffrey B.; Davis, Shirley; Brotherton, David K.; Cook, Robert; Behler, John; Connery, Bruce (Biological conservation, 2006)
We investigated and reviewed the current and historic distribution of northern dusky salamanders ( Desmognathus fuscus fuscus) in Acadia National Park (ANP), Maine, USA during 1938–2003. Historical data indicate that northern dusky salamanders were once widespread and common in ANP. We conducted intensive surveys for stream salamanders during 2000–2003 and observed only two adult northern dusky salamanders on one stream. No eggs or larvae were observed. Although the cause of the observed population decline is unknown, we identify multiple potential stressors including stocking of predatory fishes, fungal pathogens, substrate embeddedness, and widespread pollution (i.e., from atmospheric pollutants) of surface waters at ANP. Our data suggest that ANP streams may no longer be suitable for northern dusky salamanders. This investigation is the first to document the decline of a stream dwelling amphibian species in a national park (i.e., areas that are not subject to obvious habitat loss or major changes in land use) with widespread mercury contamination of its surface waters.